Examining the Antecedents, Capabilities and Performance of Sustainable Supply Chain Management Practices Across Manufacturing Supply Chains in Ghana. - Agyabeng-Mensah, Yaw (Curtin University, 2025)
Manufacturing supply chains are crucial to global economy but often detrimental to the planet and people. In Ghana, achieving sustainability is complex and essential. This study examines the roles of community sustainability orientation, supply chain motives, information exchange, leadership competency and sustainable supply chain management (SSCM) practices in achieving sustainability goals across Ghana's manufacturing supply chains. The study provides a more nuanced insight into the motives, capabilities and outcomes of SSCM practices, with implications for both theory and practice.